Discursos sobre o mal-estar e o bem-estar docente e os processos de formação e de profissionalização dos professores da educação básica - Ferreira, Marilda de Lima Oliviera (2015)
This work is linked to the Research Line Teachers’ Professionalization and Educational Practices, of the Post-graduation Program in Education, of the Education College of Federal University of Goiás-Brazil. This research has as central theme Uneasiness and Welfare of Basic Education teachers. The work is part of the ones developed by researchers on teachers profession in Brazilian Middle West (REDECENTRO), which look for enlarge knowledge about teachers. The question of this investigation, which consisted in its general objective, was proposed as follows: what is written in publications of the most important periodicals of Educational area in in Brazilian southern region (Qualis A and B), in the period 2010-2015 (first semester) about Teachers’ Welfare and Uneasiness as well as about processes of formation a professionalization of teachers? To reach this aim, we looked for answering the following specific objectives: a) understanding Brazilian public university and its now-a-days configuration as the privileged context of formation and professionalization; b) analyzing the paths of Basic Education teachers’ formation and professionalization, by considering legislation which rules these processes; c) methodically arranging and analyzing the concepts of Teachers’ Uneasiness and Teachers’ Welfare, looking for apprehending its historicity in foreigner and Brazilian publications; d) analyzing Brazilian production in periodicals of the educational area, focusing the expressed epistemological approaches and the relationships established by the authors between Teachers’ Uneasiness, Teachers’ Welfare and the processes of formation and professionalization of Teachers, in order to understanding the relationships between Welfare and Uneasiness to Basic Education Teachers’ formation and professionalization processes expressed in the publications analyzed, mainly in Revista Educacion e Realidade, Revista Por Escrito e Revista Cadernos de Pesquisa, in the period from 2010 to 2015 (first semester). The study departed from the understanding that Teachers’ Uneasiness and Teachers’ Welfare are phenomenons which cohabit dialectically in the labor processes, having its origin over the confrontation of all the conditionings of the teaching profession, mainly those related to the transformations occurred in education after the meddle of the decade of 1990. This study is a bibliographical research with a qualitative approach, with basis on the historical dialectical materialism. The authors who supported theoretically the production belong to the same critical basis, with prominence and support to the counterhegemonic political posture here assumed. Together, they supported the theoretical discussion about: 1) public university and its crisis, with origin in insertion of neoliberal ideas in education, after the 1990 years; 2) teachers’ formation and the unfolding of capitalistic ideals in policies and legislations related to that formation; 3) the concepts of Teachers’ Uneasiness and Welfare, whose construction had as aim to apprehend the historicity of the themes and conceptions produced by looking for their dialectic construction and its relationship to the processes of formations an professionalization of teachers of basic education. The theoretical construction is associated to the empirical one, which identified three papers that dealt with the subject in the considered period. The analysis made it possible to understand that the speeches constructed in the Periodicals Qualis A and B can be summarized as follows: a) teachers’ uneasiness and teachers’ welfare in basic education are not uneventful themes in those publications; b) is almost absent the discussion of these themes from a critical counterhegemonic perspective; c) there is no proposal of intervention on teachers’ uneasiness nor incentive to teachers’ welfare in teaching field of Basic Education.